2017
DOI: 10.1159/000477314
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-424 Promotes Non-Small Cell Lung Cancer Progression and Metastasis through Regulating the Tumor Suppressor Gene TNFAIP1

Abstract: Background/Aims: This study aimed to investigate the potential roles of miR-424 expression in non-small cell lung cancer (NSCLC) metastasis and growth and its underlying mechanism. Methods: The expression of miR-424 in two NSCLC cell lines (A549 and H1975) was altered by transfection with miR-424 mimic and inhibitor. Effects of miR-424 overexpression and suppression on cells migration, invasion and colony formation were analyzed. Target genes for miR-424 were predicted using bioinformatics method and then ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…38 Nevertheless, there were controversies regarding the expressional profile of miR-424 within tumors. To be specific, highly expressed miR-424 was detectable within squamous cell carcinoma, non-small cell lung cancer and pancreatic cancer, 20,39,40 yet no significant variation of miR-424 expression was observed within bladder epithelial carcinoma. 41 These discordances might be explained by that miR-424 functioned distinctly within various tissues and organs, which entailed further proofs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…38 Nevertheless, there were controversies regarding the expressional profile of miR-424 within tumors. To be specific, highly expressed miR-424 was detectable within squamous cell carcinoma, non-small cell lung cancer and pancreatic cancer, 20,39,40 yet no significant variation of miR-424 expression was observed within bladder epithelial carcinoma. 41 These discordances might be explained by that miR-424 functioned distinctly within various tissues and organs, which entailed further proofs.…”
Section: Discussionmentioning
confidence: 98%
“…14 Virtually, the lowly expressed miR-424 was discoverable in a broad array of other neoplasms, including glioma, cervical cancer, endometrial cancer, ovarian cancer, prostate cancer and lung cancer. [15][16][17][18][19][20] Viewed mechanically, miR-424 was capable of interfering with the expression of genes (i.e., Chk1) that were pivotal to the G1-S phase transition of cell cycle and infiltration of tumor cells (i.e., SiHa and CaSki cell lines). 16,21 Interestingly, targeting Chk1 could sensitize glioma cells against temozolomide, 22 which thereby insinuated a regulatory part of miR-424 in chemoresistance of glioma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Further, all results highlight that CCAT1 knockdown inhibited cell proliferation by modulating cell cycle progression and cell cycle-related proteins. Cell migration and invasion are also critical factors in tumor metastasis [27]. Zhang et al demonstrated that high CCAT1 expression closely correlates with TNM stage, differentiation grade and lymph node metastasis in breast cancer patients [28], and Zhu et al reported that CCAT1 is a potential biomarker for predicting prognosis in patients with hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, overexpression of TNFAIP1 induced by knockdown of miR-372 promoted cell apoptosis via regulation of the NF-kB signaling pathway. In HeLa cell lines, overexpressed TNFAIP1 also increased cell apoptosis via downregulation of NF-kB expression [33][34][35][36]. Thus, we selected TNFAIP1 as the final target of EHMT2-induced apoptosis.…”
Section: Epigenetic Regulation Of Tnfaip1 By Ehmt2 Induced the Apoptomentioning
confidence: 99%